Land inequality and the emergence of human capital promoting institutions - Oded Galor; Omer Moav; Dietrich Vollrath (Brown University, Department of Economics, 2005)
This research suggests that favorable geographical conditions, that were inherently associated with inequality in the distribution of land ownership, adversely affected the implementation of human capital promoting institutions (e.g., public schooling and child labor regulations), and thus the pace and the nature of the transition from an agricultural to an industrial economy, contributing to the emergence of the Great Divergence in income per capita across countries. The basic premise of this research, regarding the negative effect of land inequality on public expenditure on education is established empirically based on cross-state data from the beginning of the 20th century in the United States.
Keywords: O10; O40; 330; Land Inequality; Institutions; Geography; Human capital accumulation; Growth; Grundbesitz; Vermögensverteilung; Humankapital; Entwicklung; Institutionalismus; Bildungswesen; Schulpolitik; USA